Rhetorical Language as a Strategy in the Delivery of Friday Sermon in Brunei Darussalam) (Jurnal Bahasa, 2023)
The use of rhetorical language in da’wah writing has a certain influence and effect on the society comprehensively. Thus, the selection of rhetorical words needs to be emphasized by the sermon writer in the effort to produce quality da'wah discourse. This not only guarantees the effectiveness of the da'wah delivered, but it is also able to realize every objective outlined by the religious institution, especially in the coordination of Friday sermon text production delivered from March to May 2022. This study was done to identify the application of rhetorical language that was utilized in the production of Friday sermon texts by the religious institutions in Brunei Darussalam, with the guidance of modern rhetorical theory by Enos and Brown (1993). This study also analyzes and discusses the role and functions of the rhetorical markers that are considered as an effective da'wah strategy. Through this study, it is found that the religious institutions in this country have utilized the use of rhetorical language as the main strategy in the delivery of Fridaysermon texts by applying several rhetorical writing techniques, namely exposition, description, persuasion and argumentation. In conclusion, the success in delivering da'wah discourse to the community relies on wisdom in the use of language so that the topic to be delivered is done so easily and more clearly.Keywords: Friday sermon, rhetorical language, strategy, aesthetics,da'wah, influenceFull text: PDF